Relevance of Guy's stone score in evaluation and outcome of percutaneous nephrolithotomy - Rohit Kapoor; Deepak Mane; Siddharth Jai Singh; Vikram Satav; Vilas Sabale; Pratyush Ranjan (Current Urology)
Abstract. Objectives. This study aimed to ascertain the relevance of the Guy's stone score in the evaluation and outcome of percutaneous nephrolithotomy (PCNL). Materials and methods. This 2-year hospital-based, prospective clinical study enrolled 100 patients who were indicated for PCNL. All patients were allocated into groups according to the Guy's stone score and were compared for factors associated with stone-free rate (SFR) and complication risk. The data were statistically analyzed using SPSS version 20. Results. The median patient age was 40 years (range, 5–70 years). A greater portion of the patients were aged 31–40 years. A majority of the stones were solitary, found in 83% of the kidneys. Overall, 49% were grouped as Guy's stone score 1, 26% as 2, 11% as 3, and 14% as 4. The overall SFR was 97%. Furthermore, SFR was found to be 100% for Guy's stone score 1, 100% for 2, 90.91% for 3, and 85.7% for 4. Intraoperative and postoperative complication rates were found in 6% and 38% of the patients, respectively. Among postoperative complications, pain (26%) was the most frequent, followed by fever (8%), bleeding (3%), and puncture site abscess (1%). Conclusions. Based on the study findings, Guy's stone score was efficient in predicting PCNL outcomes.